Basic Characteristics, Status, and Challenges of Integrative Oncology in China. (December 2021) - Yang, Geliang; Zhang, Huiqing; Xu, Yun; Zhao, Aiguang; Shu, Peng; Wang, Wei; Zhang, Haibo; Wang, Tingting; Yang, Yufei
Integrative oncology has developed for about 20 years in some countries; however, integrative oncology is still a relative new term for most China's oncologists. Thus, it is essential to summarize the experience and expertise, share details of differing existing models and discuss future perspectives to help define and guide practice in integrative oncology in China. This study presents a summary of the basic characteristics, status, and challenges of integrative oncology in China, and also reports on China's integrative physicians' service delivery, clinical practice and research patterns of integrative oncology by an online national survey, including 405 oncologists. It is easy for cancer patients to access to integrative therapies in China. Public funding is sufficient for integrative oncology in China, and services are often provided through general hospitals and academic hospitals. Most (95.3%) of oncologists showed a positive attitude toward the development of integrative oncology. More than half (55.6%) of the oncologists worried about the influence on integrative oncology of COVID-19, especially for routine treatment, follow-up and holding seminars. We found that integrative oncology in China has swiftly developed in recent years. However, we suggest that standard diagnosis and treatment patterns and national professional guidelines should be set up as soon as possible.